An Ethnographic Meta-Synthesis of Three Southwestern Rural Studies - Averill, Jennifer B. (Public Health Nurs, 2015)
OBJECTIVES: The objectives were to synthesize cumulative findings across three critical ethnographic, community-partnered studies in the southwestern United States and to describe the process of meta-ethnography for that analysis. DESIGN: The meta-ethnography followed the design of Noblit and Hare for constructing an analysis of composite data, informed by community-based participatory research and Stringer’s ethnographic strategies of Look-Think-Act. SAMPLE: The three studies occurred in rural settings of Colorado and New Mexico, engaging 129 total participants, along with community organizations and agencies as partners. METHODS: Methods consisted of detailed review of each original study, mapping of major concepts and themes, and general analysis, interpretation, and synthesis across the studies. RESULTS: Overall themes were: health is the capacity to care for oneself and do work, meaningful relationships are key in health care interactions, patterns of discrimination persist in rural settings, poor literacy and health literacy are barriers, and food insecurity is a growing concern for older rural adults. CONCLUSIONS: Resolutions involve practice, policy and research and must incorporate all stakeholder groups in rural settings; a participatory approach is critical to prioritize and impact existing inequities; and work is needed to extend education and understanding of multiple cultures, groups, customs, and rural contexts.